Suva Stories A History of the Capital of Fiji - Halter, Nicholas (Pacific Series, 2022)
Suva Stories explores a fascinating tapestry of histories in one of the Pacific's oldest and most culturally diverse urban centres, the capital of Fiji. Charting the trajectory of Suva from indigenous village to colonial hub to contemporary Pacific metropolis, it draws on a rich colonial archive and moving personal memoirs that bear witness to their time. The diverse contributions in this volume form a complex mosaic of urban lives and histories that contribute fresh insights into historical and ongoing debates about race, place and belonging. Suva Stories is a valuable companion to those seeking to engage with the city's pasts and present, and will prompt new conversations about history and memory in Fiji.